The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1589/jpts.23.271
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electrical Stimulation on Blood Lactate after Anaerobic Muscle Fatigue Induced in Taekwondo Athletes

Abstract: Abstract.[Purpose] The aim of this study was to determine the effect of electrical stimulation on blood lactate after anaerobic muscle fatigue was induced in Taekwondo athletes.[Subjects] Twenty-four male collegiate Taekwondo athletes voluntarily participated in this study (from June 7, 2010 to June 18, 2010, a total of 2 weeks). Subjects were randomly divided into three groups of 8: a) Electrical stimulation group (ES) which received electrical muscle stimulation; b) the massage group which received massage; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…The NMES groups in the present study was administered a low frequency electrical stimulation during the recovery period showed a significant recovery of blood lactate and anaerobic performance as compared to control group, which is similar to the results found in previous studies [21,24,26,27,30,[38][39][40][41], although some studies have also reported contrasting findings [21,[42][43][44]. IFT used produces biphasic pulses within the tissues & has an advantage in that it does not cause skin irritation unlike some other electrical techniques [45].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The NMES groups in the present study was administered a low frequency electrical stimulation during the recovery period showed a significant recovery of blood lactate and anaerobic performance as compared to control group, which is similar to the results found in previous studies [21,24,26,27,30,[38][39][40][41], although some studies have also reported contrasting findings [21,[42][43][44]. IFT used produces biphasic pulses within the tissues & has an advantage in that it does not cause skin irritation unlike some other electrical techniques [45].…”
Section: Discussionsupporting
confidence: 90%
“…IFT used produces biphasic pulses within the tissues & has an advantage in that it does not cause skin irritation unlike some other electrical techniques [45]. NMES which uses medium frequency alternating current induces vasodilation & increase peripheral blood flow [46,47] & the suction system with an electrode has a massage effect [27]. Also the rest position during NMES favors the resynthesis of PCr [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 5-second countdown was used to signal to the participants to pedal with all of their strength for 30 seconds immediately after the command "Start." After 30 seconds, the participants were permitted active rest for 10 seconds at 60 rpm and 100 W. Verbal encouragement was given to the participants to exert maximum effort 17) .…”
Section: Methodsmentioning
confidence: 99%
“…Anaerobic activity causes fatigue because of lactic acid accumulation. Accordingly, the ability to rapidly remove accumulated lactic acid can enhance performance and reduce the risk of injury 2 ) . Furthermore, heart rate recovery is a controversial issue, and obesity level could impact heart rate recovery 3 ) .…”
Section: Introductionmentioning
confidence: 99%